Towards living well with young onset dementia: An exploration of coping from the perspective of those diagnosed. (July 2014) - Clemerson, Gemma; Walsh, Sue; Isaac, Claire
There is increasing recognition that dementia in people under 65 years represents a unique challenge to sufferers and services alike. However, by either ignoring this population or sampling them together with older adults, current research has failed to reflect this. This study explored the specific experience of living and coping with Alzheimer's disease in younger life from the perspective of those diagnosed. Semi-structured interviews were analysed using interpretive phenomenological analysis, and four themes were identified: 'disruption of the life-cycle', 'identity', 'social orientation' and 'agency'. The experience of living and coping with young onset Alzheimer's disease was strongly situated within an individual's social context. Most significantly, participants felt too young to develop the disease and felt out of time with age-related psychological tasks. Coping strategies that attempted to redress and normalise the life-cycle were identified. The contributions of the study are discussed in the context of the human development literature.